Generating Adaptation Plans Based on Quality Models for Cloud Platforms - Silva, Jorge Luiz Machado da; França, Breno Bernard Nicolau de; Rubira, Cecília Mary Fischer (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2020: Anais do XXXIV Simpósio Brasileiro de Engenharia de Software, 2020)
Cloud computing brought up several benefits concerning cost and scale, offering support services for infrastructure provisioning targeting data processing and storage according to application demands. However, it is not trivial to ensure the trustworthiness of associated resources, i.e., the trust of a client in a cloud service and its provider. Hence, one of the main barriers is to warrant the nonfunctional properties of trustworthiness during runtime. This paper presents a new infrastructure to generate adaptation plans based on quality models to ensure different trustworthiness properties. On detecting the degradation of cloud resources regarding the monitored properties, an adaptation plan is generated and executed during runtime to ensure that cloud resources can work under proper trustworthiness levels. The proposed solution intends to be general, possibly being applied to several trustworthiness properties simultaneously. Finally, we evaluated the solution in a feasibility study under a scenario considering data privacy and performance as trustworthiness properties.